Purification and characterization of acidic fibroblast growth factor from bovine brain. - Thomas, K A (1984)
Acidic brain fibroblast growth factor has been purified a minimum of 35,000-fold to apparent homogeneity by a combination of differential salt precipitation, ion exchange chromatography, gel filtration, isoelectric focusing, and hydrophobic chromatography on a C4 reversed-phase HPLC column. Two microheterogeneous forms of the molecule are obtained with apparent molecular masses of 16,600 and 16,800 daltons. The mitogen is highly active with half-maximal stimulation of BALB/c 3T3 fibroblasts at about 40 pg/ml in an assay using incorporation of [methyl-3H]thymidine into DNA.